2002
DOI: 10.12702/1984-7033.v02n03a06
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability in baby corn inbred lines (Zea mays L.)

Abstract: Seven baby corn inbreds were crossed in a complete diallel scheme. The single-cross hybrids obtained were assessed at the São Manuel Experimental Station, in São Paulo State, Brazil. The experiment was set up in a randomized complete block design with three replications, including one commercial control. The experimental plots consisted of a single row, 5 m long, with 25 plants. The traits assessed were: number of ears/plot, weight, length and diameter of husked and dehusked ears, plant height and ear height. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
4
8
1
Order By: Relevance
“…The estimate of the coefficient of variation (Table 2) for this trait is consistent with that observed by Rodrigues and Silva (2002). The estimated value of selection accuracy for this trait fits into the class of experimental precision very high (Resende and Duarte 2007).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The estimate of the coefficient of variation (Table 2) for this trait is consistent with that observed by Rodrigues and Silva (2002). The estimated value of selection accuracy for this trait fits into the class of experimental precision very high (Resende and Duarte 2007).…”
Section: Resultssupporting
confidence: 83%
“…The coefficients of variation (Table 2) for EL and ED were similar to those reported by Rodrigues and Silva (2002). The coefficient of variation for EY was similar to that observed by DoVale et al (2011), when evaluating 10 commercial maize cultivars suited for baby corn production.…”
Section: Resultssupporting
confidence: 78%
“…So these parents could be used extensively in hybrid breeding program to improve baby corn yield and its quality. Dhasarathan et al (2015) and Rodrigues and da Silva (2002) also observed and verified significant positive number of baby corns per plant, baby corn length, baby corn weight and baby corn yield per plot. None of the parents showed significant positive GCA effects for ear length, which is supported by Rodrigues and da Silva (2002) and opposed by Dhasarathan et al (2015).…”
Section: General Combining Ability (Gca) Effectsmentioning
confidence: 85%
“…Similar finding were reported by Ceyhan et al [6], Kanagarasu et al [7] and Motamedi et al [8] and Ahmed et al [9] in corn for different characters. Involvement of non-additive gene action for the characters in present investigation is also in consonance with the findings of Suneetha et al [10] for days to 50% tasselling and silking, Dhasarathan et al [11] for days to 50% tasseling, plant height, number of baby corns per plant, baby corn length, baby corn weight, Anantha [12] and Selvarani [13] for days to tasseling, Geetha and Jayaraman [14], Anantha [12] and Prakash and Ganguli [15] for plant height, Rodrigues and Da Silva [16] for baby corn length, Mahto and Ganguly [17] for grain yield.…”
Section: Analysis Of Variancementioning
confidence: 54%
“…KH-101/S 3 -44 expressed highly significant positive GCA effects for weight of per cob with husk. Dhasarathan et al [11] and Rodrigues and Da Silva [16] also observed significant positive number of baby corns per plant. None of the parents showed significant positive GCA effects for cob diameter, which is supported by Rodrigues and Da Silva [16] and opposed by Dhasarathan et al [11].…”
Section: General Combining Ability (Gca) Effectsmentioning
confidence: 94%